The day-to-day relationship between posttraumatic stress symptoms and social support after sexual assault - Esther S. Howe; Emily R. Dworkin (European Journal of Psychotraumatology, 2024)
ABSTRACTBackground: Experiencing sexual assault is associated with a significant increase in risk for developing posttraumatic stress disorder and related concerns (e.g. alcohol misuse). Cross-sectional and longitudinal evidence suggests that social support may be both broadly protective against and eroded by posttraumatic stress symptoms. However, little is known about how different aspects of social support and posttraumatic stress symptoms influence each other in the weeks and months immediately following sexual assault, when posttraumatic stress (PTS) symptoms first emerge.Objective: The present study assessed the day-to-day relationship between social support and PTS in a sample of distressed, alcohol-using, recently-assaulted female survivors participating in a clinical trial of an app-based intervention (N = 41).Method: Participants completed 3 weeks of daily diaries starting within 10 weeks of sexual assault. Mixed-effects models were used to examine prior-day and same-day relationships between PTS and four social support constructs (social contact, emotional support, pleasantness of social interactions, and talking about sexual assault).Results: Results indicate that higher quantity and pleasantness of social interactions over the full sampling period was associated with lower PTS symptoms on any given day. Experiencing better-than-typical social interactions on one day was associated with lower than typical PTS symptoms on that day and the next day. On days when participants discussed their sexual assault with others, they tended to be having higher than usual PTS symptoms.Conclusions: Findings suggest that increasing the quantity and pleasantness of social interactions soon after sexual assault might protect against worsening posttraumatic stress symptoms.Trial registration: ClinicalTrials.gov identifier: NCT03703258.